Surgical resection of a congenital hemangiopericytoma involving the thoracic spine - Chang Hun Kim; Joohyung Son; Do Hyung Kim; Sung Kwang Lee; Bong Soo Son (Journal of Pediatric Surgery Case Reports, 2019)
A congenital hemagiopericytoma (HPC) is an uncommon tumor derived from vascular pericytes; HPCs involving the central nervous system are rare. No report of a congenital HPC involving the spinal cord has yet appeared. Most adult HPCs become malignant, but infantile HPCs are benign. However, resection is necessary because the tumors grow rapidly and the risk of spontaneous bleeding is high. We here report a congenital HPC involving the back, thoracic cavity, and spinal cord. This is the first report of a congenital HPC that invaded the spine. Keywords: Hemagiopericytoma, Chest wall mass, Intrathecal mass